A Case of Spontaneous Tumor Lysis Syndrome in a Patient with Ovarian Cancer - Kazuhiro Okamoto; Toshifumi Kinoshita; Miyuki Shimizu; Isoji Okura; Akinori Kawada; Koichi Mizobuchi; Midori Ando (Hindawi Limited, 2015)
Tumor lysis syndrome (TLS) is a potentially life-threating complication of tumors or chemotherapy treatment. TLS commonly occurs in hematological malignancies, but it is very rare in patients with a solid tumor. In cases of solid tumors, TLS usually occurs spontaneously and after the initiation of anticancer therapy, and it has a high mortality rate. We present the novel case of a 62-year-old woman with an ovarian tumor who spontaneously developed TLS. Surgical reduction of the tumor mass vastly improved her condition. She showed no sign of tumor recurrence 8 months after treatment. As TLS is life-threatening, successful treatments must be seriously considered.